Columbo : The Complete Season 2 Disc 3-4 - Steven Spielberg; Falk, Peter; Jack Cassidy; Rosemary Forsyth; Product Details; Barbara Colby (USA Universal Studios, 1971)
Universal has released the sophomore season (1972-73) of the classic detective series Columbo, starring Peter Falk as the sage but rumpled police lieutenant. As with the first season, there's plenty of star power in front of and behind the camera to abet Falk in these eight 90- and 120-minute episodes: John Cassavetes stars in the season premiere, Etude in Black, as a philandering symphony conductor, with Blythe Danner and Hollywood legend Myrna Loy in support; Oscar winner Ray Milland is a scheming orchid grower in "The Greenhouse Jungle," co-starring Bradford Dillman and William Smith; Robert Culp and Dean Stockwell are a football team manager and owner, respectively, whose disagreements blossom into murder in "The Most Crucial Game"; and Jeanette Nolan offers stellar comic relief in "Double Shock," which features Martin Landau as identical twins--one of whom has murdered their uncle. Performances by Richard Basehart, Laurence Harvey, Leonard Nimoy, Anne Francis, Anne Baxter, and Mel Ferrer also highlight the season; direction by small-screen stalwarts like Boris Sagal, Jeremy Paul Kagan, and Nicholas Colasanto ("Coach" on Cheers) and scripts by Stephen Bochco also bring quality and style to the proceedings. Sadly, no extras are available in this five-disc set, but the stellar image and sound quality (and lack of commercials) should appeal to series fans and newcomers alike.
Languages: English, French, Italian, German, Spanish Subtitles: English, French, Italian, German, Spanish, Danish, Dutch, Finnish, Norwegian, Swedish
Keywords: Crime; Drama; Mystery -- TV Series